1987
DOI: 10.2214/ajr.149.6.1195
|View full text |Cite
|
Sign up to set email alerts
|

Renovascular hypertension caused by compression of the renal artery by the diaphragmatic crus

Abstract: (Fig. 1 B)and only spot films were obtained. A severe crural impression on the celiac axis was also a finding on the lateral aortogram.The anglographcflndings suggested congenital web or band compressing the artery. On a separate day, renal vein samples for renin levels were obtained by using captopril stimulation.These values were 75 ng/ml/hr on the right, 109.2 ng/mI/hr on the left, and 30.9 ng/ml/hr in the inferior vena cava below the renal veins. An initial renal scan using "Tc-DTPA was normal. A repeat re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…Compression of the renal artery by the crura has been recognized as an unusual cause for renal artery stenosis and renovascular hypertension (58). An atypical high and posterior origin of the left renal artery appearing entrapped within the RCS by the diaphragmatic crus can be adequately recognized with contrast-enhanced helical CT and especially with CT angiography (59) (Fig 24).…”
Section: Vascular Disorders-mentioning
confidence: 99%
“…Compression of the renal artery by the crura has been recognized as an unusual cause for renal artery stenosis and renovascular hypertension (58). An atypical high and posterior origin of the left renal artery appearing entrapped within the RCS by the diaphragmatic crus can be adequately recognized with contrast-enhanced helical CT and especially with CT angiography (59) (Fig 24).…”
Section: Vascular Disorders-mentioning
confidence: 99%
“…On literature review, two cases of vein patch were performed after inspection of the intima showed no irregularity. 4,8 There was one aortorenal saphenous vein bypass without MAL decompression. This was complicated by graft thrombosis, resulting in postoperative recognition of the extrinsic compression.…”
Section: Discussionmentioning
confidence: 99%
“…Although angioplasty and stenting of visceral arteries seems to be successful in the setting of atherosclerosis, their use in the setting of CACS has been questioned because of the presence of extrinsic compression. 17,22 The increasing applicability of stent deployment for mesenteric occlusive disease has given interventional radiologists the opportunity to expand the use of PTA and stenting to patients with CACS before primary surgical intervention. However, the few attempts of angioplasty and stenting patients with entrapment of renal arteries by diaphragmatic crura are not convincing.…”
Section: Discussionmentioning
confidence: 99%